CORPORATE INNOVATION: EXPLORING ORGANIZATIONAL PERFORMANCE IN COMMERCIAL BANKS, ABIA STATE, NIGERIA - Maxwell Nwinye (Journals Park Publishing, 2025)
This study examined corporate innovation and organizational performance in commercial banks in Abia State, Nigeria. The researcher applied two measures of corporate innovation such as process innovation and market innovation. Two proxies of organizational performance namely customer satisfaction and market share were illustrated in the study. Population of the study encompasses 190 selected employees from six reachable commercial banks in Abia State, Nigeria. A survey research design and purposive sampling method were utilized. Both primary and secondary data were adopted with the aid of questionnaire. Chosen participants were managers and senior staff selected from commercial banks. The researcher used Taro Yamane’s formula to get 129 sample size of employees. Copies of questionnaire were circulated as research instrument for this study. The questionnaire was structure in ordinal scale. Statistical instrument used in this study was Spearman rank correlation coefficient to test the hypotheses. The findings proved that process innovation has significant positive relationship with customer satisfaction. It was concluded that corporate innovation influences organizational performance in commercial banks. The researcher recommends that commercial banks should encourage process innovation in other to enhance customer satisfaction.
Keywords: Corporate innovation, process innovation, market share, organizational performance